The Lotus transcather aortic valve: a next-generation repositionable, resheathable and recapturable prosthesis. (August 2014) - Gooley, Robert; Antonis, Paul; Meredith, Ian
Symptomatic severe aortic stenosis occurs in 2–4% of people aged over 65 years, with calcific degeneration being the predominant etiology in the developed world. Surgical valve replacement has been and remains the gold-standard treatment modality, yet a significant number of high-risk individuals are denied or refuse this potentially life-saving treatment. Transcatheter aortic valve replacement has proven efficacy in this high-risk cohort. Current-generation transcatheter aortic valve replacement devices, however, have significant limitations. The Lotus transcatheter device represents an evolution of this technology that allows full resheathing, repositioning and retrieval, which together with features designed to minimize para-prosthetic regurgitation address a number of the limitations of first-generation devices.